News media literacy skills and violence against women in news reporting in Turkey: instrument development and testing. (2nd September 2019) - Alagözlü, Nuray; Koban Koç, Didem; Ergül, Hatice; Bağatur, Sümeyra
Abstract: The purpose of the present study was twofold: The first was to determine the validity and reliability of a news media literacy questionnaire that was developed to identify college students' literacy levels related to media and news about violence against women. The existing literature about media literacy shows that there is a lack of evaluation instrument of this kind. The study aimed to determine whether or not Turkish students could critically analyze the news reports, in particular, news about violence towards women, given on different news channels. A questionnaire that consisted of 16 questions divided among three categories (awareness, analysis, and judgment) was developed based on a comprehensive review of related studies in the literature. Data were collected from 172 Turkish college students enrolled in the department of English Language Teaching at a major government university in Turkey. The results showed the instrument to be reliable and valid. The second aim of the study was to validate the questionnaire with 81 laypersons of different age groups and with different educational and income levels. The results of the validation study were given as a preliminary presentation of the perceptions of the respondents.